Manajemen Aktivitas Fisik dan Kepatuhan Minum Obat untuk Mencegah Terjadinya Hipertensi pada Penderita Diabetes Melitus Tipe II - Gracilaria Puspa Sari; Marek Samekto; M. Sakundarno Adi (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
Patients with type 2 DM are more at risk of developing hypertension. This study aims to explain the factors that afect the occurrence of hypertension in patients with type 2 diabetes in the work area of Pati Puskesmas during 2014. The study was conducted by observation using a case control study design in Puskesmas patients in Pati District. The case group was 57 patients with type 2 diabetes with hypertension while the control group was 57 patients with type 2 diabetes without hypertension. Data were obtained from observations of medical recordsand qualitative interviews. Chi-square test on bivariate analysis and multiple logistic regression on multivariate analysis. Factors afecting the occurrence of hypertension in patients with type 2 diabetes are less physical activity (OR = 6.4, 95% CI: 2.18 - 18.77, p = 0.001), long sufering DM â‰¥5 years (OR = 5, 4, 95% CI: 1,97 - 14,704; p = 0,001), and DM medication adherence (OR = 3,6; 95% CI: 1,32 - 9,83; p = 0,012). Factors that have no efect are: age â‰¥45 years,male gender, DM diet compliance, history of hypertension, smoking habits, salty eating habits, cofee drinking habits, and length of time to sleep. Type 2 diabetes mellitus patients> 5 years may reduce the risk of hypertension by performing physical activity management and medication adherence.Keywords: risk factor, hypertension, type 2 DM